Penerapan Konsep Healing Environment Pada Perencanaan Public Healing Center di Desa Batuan, Sukawati, Gianyar, Bali: Bahasa Indonesia - Ni Putu Cahaya Suksema Dewi; I Nyoman Gede Maha Putra; Made Suryanatha Prabawa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
A Public Healing Center is defined as a place or healing center for people with mental health disorders that involve the psychological effects of the patient in it. There are three approaches used in designing a healing environment, namely natural, sensory and psychological. The number of sufferers of mental health disorders in Indonesia is quite high, therefore it is necessary to have an environmental area for people with complaints or mental health disorders to be able to